Sistem Pakar Online untuk Mengidentifikasi Hama pada Tanaman Jeruk - Rahmawati, Yunianita; Yustiana, Diyah; Asmoro, Ruli Widya (Jurnal Ilmiah Teknologi Informasi Asia, 2012)
An orange commodity can improve level live society. Till now orange product not yet fulfilled expectation. This matter because of the limited knowledge [all] farmer in the case of having real correct orange cultivation to and pest appearance and disease. Lack of orange crop pest information cause all farmer of difficulty in detecting early pest symptom and his operation so that effectively can do] needed actions, particularly with many generated symptoms him. This matter often makes farmer become a difficulty in searching correct decision. One of the ways of to assist the farmer in determining pest type is to utilize the expert system with a method of forward chaining. By exploiting availability broadness and usage of internet give the opportunity to propagate knowledge and membership about identifying orange pest to many people.